Adopting Technological Pedagogical Content Knowledge in Muhammadiyah Higher Education Institutions: Benefits and Challenges - An'guna Bansa, Yorina; Sulistiyo, Urip; Ayu Wulandari, Bunga; Abrar, Mukhlash; Ballikaya, Sedat (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study aimed to reveal challenges and benefits that lecturers may face when integrating TPACK in their classrooms. A qualitative approach was employed to gain insight into this study. The participants in this study were English lecturers in Muhammadiyah Higher Education Institutions in Jambi province, Indonesia. There were eight participants in this study. The instruments of this study were individual semi-structured interviews. The technique of data collection was to transcribe the results of the interview. This study used a thematic approach to analyse the data. The thematic analysis of this study involved coding every meaningful statement in the interview transcription data. This study revealed the benefits and challenges of adopting TPACK. The benefits were encouraging students’ motivation, supporting an adaptable and pleasant classroom, and facilitating the lecturer’s creativity. Additionally, the challenges were supporting system, digital literacy, and time constraints. This study fulfills the research gap regarding the contributors and the area of research. The contributors are the lecturers who teach for the English department and the lecturers who teach for non-English department students. The area of this research was in higher education and in the classroom context.